Development and testing of an aerosol/stratus cloud parameterization scheme for middle and high latitudes. Final technical progress report, November 1, 1994--October 31, 1998 - Kreidenweis, S. M.; Cotton, W. R. (Colorado State University. Department of Atmospheric Science., 1999)
At the present time, general circulation models (GCMs) poorly represent clouds, to the extent that they cannot be relied upon to simulate the climatic effects of increasing concentrations of greenhouse gases, or of anthropogenic perturbations to concentrations of cloud condensation nuclei (CCN) or ice nuclei (IN). The long-term objective of this research was the development of an aerosol/cloud microphysics parameterization of mixed-phase stratus and boundary-layer clouds which responds to variations in CCN and IN. The work plan was to perform simulations of these cloud systems to gain understanding of their dynamics and microphysics, especially how aerosols affect cloud development and properties, that cold then be used to guide parameterizations. Several versions of the CSU RAMS (Regional Atmospheric Modeling System), modified to treat Arctic clouds, have been used during the course of this work. The authors also developed a new modeling system, the Trajectory Ensemble Model, to perform detailed chemical and microphysical simulations off-line from the host LES model. The increased understanding of the cloud systems investigated in this research can be applied to a single-column cloud model, designed as an adaptive grid model which can interface into a GCM vertical grid through distinct layers of the troposphere where the presence of layer clouds is expected.